Insect Pollinator’s Role in Fruit Setting of Prosopis cineraria (L.) Druce - Bhatnagar, Shiwani; Khan, Ameen Ullah; Rathore, Lokendra Singh; Sharma, Neha (International Journal of Economic Plants, 2022)
The experiment was conducted in the Ecology Field, Arid Forest Research Institute, Jodhpur (Rajasthan), India during 2020-21 to explore the role of insect pollinators in the fruit setting of P. cineraria. For conducting the experiments one of the branches of the selected trees was covered with a mesh bags to exclude floral visitors (pollinator exclusion). The other branch was kept uncovered for the time of the experiment (open pollination). Our findings revealed that the average fruit set under pollinator exclusion (bagged condition) was nil whereas it was 2.02% in open natural pollination. This study confirms previous studies that P. cineraria is a cross–pollinated species. Also, average moisture content was found to be 10.75 % in seeds and 49.21% average carbohydrate content in pods under open pollination, germination percentage was found to be 71.3% and seedling vigour index was 655.2. Present study also calculated the average seed weight, average seed length, average seed breadth, average seed thickness obtained in above experiment.